Fire safety in commercial plastic recycling facilities - Devine, Courtney Kaylor (Stellenbosch University, 2025)
Devine, C. K. 2025. Fire safety in commercial plastic recycling facilities. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/ecf8c879-18c6-45e5-abee-2d67a87807e2